Peace Education and Human Rights Literacy as Tools for Conflict Prevention in the Niger Delta: A Human Security Perspective (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Nigeria’s Niger Delta is one of the regions of the world that recorded intractable conflicts over the years. The spasmodic violence, instability and conflict in the region are as deeply rooted in socio-economic marginalization, environmental degradation, human rights violations and governance failure. Consecutive decades of state interventions and corporate social responsibility have not ensured peace as sustainable and enduring. This indicates the weakness of conventional, state-led conflict management. This paper examines how peace education and human rights literacy can be employed as transformative tools of conflict prevention in the Niger Delta from the perspective of a human security framework that prioritizes people-focused solutions over militarized solutions. Drawing on qualitative data from policy reports, field reports and interviews with stakeholder groups, the study examines how empowering local communities through awareness of their rights, building a culture of dialogue and practising peace education via formal and informal institutions can reverse the structural causes of conflict. The study affirms that improved human rights consciousness and comprehensive peace education curricula increase social cohesion, participatory governance and de-motivation of violence as conflict resolution strategies. Integration of human security ideas into peace education and rights literacy education is required to build lasting peace, environmental justice, and fair development in oil-producing Niger Delta societies.